Efficacy Analysis of Different Modes of Learning in Undergraduate Courses During and Post COVID-19 Pandemic - Devi, M. Tirumala; Afreen, Sameena; Majeed, Abdul; Prasad, V. Shyam; Reddy, G. Mahender (Communications in Mathematics and Applications, 2025)
Prior to COVID-19, taking undergraduate courses Online was an added option. Most of the universities in Telangana offered classes in Physical mode prior to COVID-19, Online mode during COVID-19, and have been currently offering classes in Hybrid mode. The current study aims at analyzing a variety of elements from the perspectives of Online education to assess the quality as well as its effectiveness in undergraduate courses that are widely practiced in most of the colleges of Telangana State, India due to the unprecedented challenges posed by the pandemic. The present study would like to focus on the administrators of e-learning platforms, teachers, and learners. To compare the relative weights of various elements while comparing Hybrid learning, Virtual learning, and Physical learning, the Analytical Hierarchy Process (AHP) approach was utilized. The results of this study can also serve as the foundation for evaluating hybrid, online, and offline learning in undergraduate courses.
Keywords: Analytical Hierarchy Process; Fuzzy AHP; Triangular Fuzzy AHP; TOPSIS method; Comparison analysis; Sensitivity analysis